Synthesis of Hierarchical BiOBr Nanostructure Flowers by PVP-Assisted Hydrothermal Method and Their Photocatalytic Activities - Anukorn Phuruangrat (2020)
© 2019, The Minerals, Metals & Materials Society. Hierarchical BiOBr nanostructure flowers as a visible-light-driven photocatalyst were synthesized by the polyvinylpyrrolidone (PVP)-assisted hydrothermal process. The role of PVP content on product morphologies and photocatalytic activities for photodegradation of rhodamine B (RhB) under visible light irradiation was studied. The as-synthesized nanostructure BiOBr samples were characterized by x-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Raman spectrophotometry, scanning electron microscopy (SEM), transmission electron microscopy (TEM) and x-ray photoelectron spectroscopy. XRD patterns of the products were used to identify the well-defined pure tetragonal BiOBr phase. SEM and TEM images showed that the as-synthesized BiOBr without PVP adding was uniform square BiOBr nanoplates with edge length of 1–3 μm. Upon adding 1.00 g of PVP 10 kDa, the uniform square BiOBr nanoplates were transformed into hierarchical BiOBr nanostructure flowers with a size of 3–4 μm. FTIR and Raman spectra of hierarchical BiOBr nanostructure flowers were used to reveal the presence of Bi-O and Bi-Br stretching vibration modes. The photocatalytic activity of hierarchical BiOBr nanostructure flowers was 96.10% degradation of RhB under visible light within 180 min. Formation mechanism of hierarchical BiOBr nanostructure flowers was also proposed according to the experimental results.